Spatial patterns of eastern Mediterranean climate influence on tree growth. (April 2014) - Touchan, Ramzi; Anchukaitis, Kevin J; Shishov, Vladimir V; Sivrikaya, Fatih; Attieh, Jihad; Ketmen, Muzaffer; Stephan, Jean; Mitsopoulos, Ioannis; Christou, Andreas; Meko, David M
The first large-scale network of 79 tree-ring chronologies in the Eastern Mediterranean and Near East (EMNE; 33°N–42°N, 21°E–43°E) is described and analyzed to identify the seasonal climatic signal in indices of annual ring width. Correlation analysis and cluster analysis are applied to tree-ring data and gridded climate data to assess the climate signal embedded in the network in preparation for climate field reconstructions and formal proxy/model intercomparison experiments. The lengths of the 79 combined chronologies range from 89 to 990 years. The monthly correlations and partial correlations reveal a pervasive positive association with May, June, and sometimes July precipitation, positive correlations with winter and spring (December through April) temperatures, and negative relationships with May through July temperature, although as expected, there are site-to-site exceptions to these general patterns. Cluster analysis suggests three groups of sites based on their association with climate. The chronologies for the EMNE have coherent seasonal precipitation and temperature signals across a fairly broad geographical domain. The predominant signal is a positive growth response to May–June precipitation. Collectively, the findings suggest that the network can be exploited to develop season-specific field reconstructions of precipitation and drought history in the EMNE.